Research of Image Compression Based on Quantum BP Network - Qi-gao Feng; Hao-yu Zhou (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Quantum Neural Network (QNN), which integrates the characteristics of Artificial Neural Network (ANN) with quantum theory, is a new study field. It takes advantages of ANN and quantum computing and has a high theoretical value and potential applications. Based on quantum neuron model with a quantum input and output quantum and artificial neural network theory, at the same time, QBP algorithm is proposed on the basis of the complex BP algorithm, the network of a 3-layer quantum BP which implements image compression and image reconstruction is built. The simulation results show that QBP can obtain the reconstructed images with better quantity compared with BP in spite of the less learning iterations. DOI : http://dx.doi.org/10.11591/telkomnika.v12i1.3908